Karakteristik Wirausaha dan Spiritualitas sebagai Penentu Keberhasilan Usaha UMKM di Jawa Barat - Khatimah, Husnul Khatimah (JRAK: Journal of Accounting Research and Computerized Accounting, 2021)
This study aims to see the contribution of entrepreneurial characteristics or entrepreneurial characteristics and Muslim entrepreneurial characteristics in determining the success of MSMEs in West Java. The research population is spread across West Java, but specifically in Bekasi and Bandung and Cimahi. The results showed that Muslim entrepreneurial characteristics and entrepreneurial characteristics were able to explain the dependent variable, namely business success at 85.5%, while the remaining 14.5% were explained or influenced by other variables. The result of Goodness of Fit (GoF) is 0.806 which is greater than 0.38, meaning that the model built has a good Goodness of Fit. Thus doing the analysis stage of testing R-Square, Q-Square and Goodness of Fit, it can be said that the model formed is robust. The influence of the Muslim Entrepreneur Characteristics variable on the Business Success variable has a medium level of influence because it exceeds the value of 0.35, which is 2,675. Likewise, the entrepreneurial characteristic variable has a weak level of influence on the business success variable with a value of 0.012 because it is less than a value of 0.2. Thus, it means that ideally they believe that these two characteristics should be possessed by entrepreneurs, but in their perception and implementation they have not implemented them properly. Keywords: entrepreneurial characteristics, Muslim entrepreneur characteristics, business success.